Studying interactions between dendritic cells and T cells in vivo. (June 2019) - Chudnovskiy, Aleksey; Pasqual, Giulia; Victora, Gabriel D
Highlights: Physical interaction with DCs is the first step in T cell priming, and controls the magnitude and quality of the ensuing response. Intravital microscopy has helped elucidate many of the key principles of T cell–DC interaction. Emerging technologies have expanded our ability to study T cell priming by DCs in situ and in vivo . Abstract : Antigen presentation is the key first step in the establishment of an antigen-specific T cell response. Among professional antigen presenting cells (APCs), dendritic cells (DCs) are the major population responsible for the priming of both CD4 + and CD8 + naïve T cells. This priming requires physical interaction between the DC and the T cell; during which signals are exchanged that determine both the magnitude and the quality of the ensuing response. The nature of these signals varies widely depending on the nature of the antigen, the anatomical site in which they take place, and the phenotype of the antigen-presenting DC, making the study of the dynamics, microanatomical distribution and phenotypic variation of DCs a key part of our understanding of adaptive immunity. Here, we provide a brief survey of how our view of T cell activation by DCs has evolved over recent years as intravital multiphoton microscopy and other emerging technologies have expanded our ability to study these events in vivo .